Avaliação da disponibilidade hídrica e da demanda hídrica no trecho do Rio Piranhas-Açu entre os açudes Coremas-mãe D´água e Armando Ribeiro Gonçalves - Moura, Eulina Maria de (2007)
Piranhas-Açu basin is a Federal watershed with a drainage area of 43.681,5 km2, sited at Brazilian northeast semi arid, with 60% of your area in Paraiba State and 40% in Rio Grande do Norte State. The main river, Piranhas-Açu, has strategic importance for development of these states, because it s an essential source for many socio-economics activities developed along watercourse. The river s reach between Coremas-Mãe D`água Dam and Armando Ribeiro Gonçalves Dam has many irrigation projects, and supply many riverside cities. All this activities practiced in this river s reach consumes high water volumes. Due the importance of this stream and the necessity of an adequate management, this work aims for an impartial and detailed evaluation of real water supply conditions in this river s reach, by the application of hydrological modeling, including the arrangement of main dams in tributaries, and storage reservoir water balance. The rainfall-discharge model s applied in each sub-basins it was selected the model MODHISA- Hydrological Model of Semi Arid, that is a concentrated model with easy application. The simulation produced 50 years of inflows into the reservoirs, for which, were constructed the guaranties curves; and produced 50 years of synthetic discharge data in relevant points on the river and on its affluents; so it was constructed the permanence curves. Confronting the available discharge with the current and futures volumes of raw water captured in this river s reach, it was verified that de demands have high guaranties. This work concluded that the MODHISA Model is suitable to reproduce the hydrologic characteristics of Piranhas-Açu sub-basins, and showing good results